The kinetics of swelling in block copolymer thin films during "solvo-microwave'' and solvo-thermal annealing: The effect of vapour pressure rate - Mokarian, Parvaneh; Morris, Michael; Collin, T.W. (My University, 2015)
We have studied the kinetics of swelling in block copolymer thin films by monitoring the pressure and temperature in situ during “solvo-microwave”[1] and solvo-thermal annealing. The results on poly (styrene-b-lactic acid) PS-b-PLA thin film suggest that it’s not the absolute value of the pressure (of THF here) and the temperature during annealing, but rather the rate at which the THF pressure increases is the key factor to obtain a good ordered pattern (see figure 1). At the next step, to show the kinetics effect, we have changed the heating rate in the oven. We will discuss that the rate of heating has a dramatic effect on the final morphology of the film. To our surprise, the fast heating rate (2-5 ⁰C/min) in the oven at the early stage of annealing provides a good order with long average line length. Slower heating rate (< 1⁰C/min) lead to a poorly phase separated structure. The highly ordered patterns are a kinetically trapped structure rather than a thermodynamic equilibrium state
APS Meeting Anbstracts
Physical Aspects of Polymer Science
Keywords: Block copolymer thin films; Solvo-thermal; Solvo-microwave; Vapour pressure rate